"We could be good partners if we work together": the perspectives of health and social service providers on the barriers to forming collaborative partnerships with social housing providers for older adults - Christine L. Sheppard; Sarah Gould; Sara J. T. Guilcher; Barbara Liu; Elizabeth Linkewich; Andrea Austen; Sander L. Hitzig (BMC, 2022)
Abstract Background Many older adults are aging-at-home in social housing. However, the lack of integration between housing and health services makes it difficult for older tenants to access needed supports. We examined barriers and facilitators health and social service providers face providing on-site services to older tenants. Methods We conducted semi-structured qualitative interviews and focus groups with health and social service professionals (n = 58) in Toronto, Canada who provide community programs in support of older tenants who live in non-profit, rent-geared-to-income social housing. Interviews examined the barriers they faced in providing on-site services to older tenants. Findings Service providers strongly believed that collaboration with on-site housing staff led to better health and housing outcomes for older tenants. Despite the recognized benefits of partnering with housing staff, service providers felt that their ability to work effectively in the building was dependent on the staff (particularly the superintendent) assigned to that building. They also identified other barriers that made it difficult to work collaboratively with the housing provider, including staffing challenges such as high staff turnover and confusion about staff roles, a lack of understanding among housing staff about the link between housing and health, challenges sharing confidential information across sectors, and complex and inefficient partnership processes. Conclusion Older adult tenants are increasingly vulnerable and in need of supports but the housing provider has a long history of ineffective partnerships with service providers driven by complex and inefficient staffing models, and an organizational culture that questions the role of and need for partnerships. Findings highlight the need for more effective integration of housing and health services. Simplified processes for establishing partnerships with service agencies and more opportunities for communication and collaboration with housing staff would ensure that services are reaching the most vulnerable tenants.